2020
DOI: 10.3390/microorganisms8091442
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Nitrogen Cycling in Antarctic Soils

Abstract: The Antarctic continent is widely considered to be one of the most hostile biological habitats on Earth. Despite extreme environmental conditions, the ice-free areas of the continent, which constitute some 0.44% of the total continental land area, harbour substantial and diverse communities of macro-organisms and especially microorganisms, particularly in the more “hospitable” maritime regions. In the more extreme non-maritime regions, exemplified by the McMurdo Dry Valleys of South Victoria Land, nutrient cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 137 publications
1
20
0
Order By: Relevance
“…The 796 MAGs obtained in the present study by a manual binning and curation effort represent one of the largest genomic catalogues of microorganisms from tundra soils to date. Earlier genecentric investigations have demonstrated the potential for complete denitrification in tundra soils [22,79], however, these approaches fail to reveal the wider genomic context of the genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 796 MAGs obtained in the present study by a manual binning and curation effort represent one of the largest genomic catalogues of microorganisms from tundra soils to date. Earlier genecentric investigations have demonstrated the potential for complete denitrification in tundra soils [22,79], however, these approaches fail to reveal the wider genomic context of the genes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of denitrifier diversity in the tundra have been largely limited to gene-centric surveys using microarrays, amplicon sequencing, qPCR, and read-based metagenomics, which provide limited information on the taxonomic identity and genomic composition of community members. These studies have shown that denitrifier communities in the tundra are dominated by members of the phyla Proteobacteria, Actinobacteria, and Bacteroidetes, and that the potential for complete denitrification is usually present at the community level [25][26][27][28][29]. However, it is not known whether the complete denitrification potential occurs within discrete microbial populations or is widespread throughout populations of truncated denitrifiers lacking one or more denitrification genes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies related to the N-cycling functional markers in Antarctica have focused on the core genes involved in N-fixation, nitrification, and denitrification processes [47]. Nitrate is, here, predicted to be reduced through two dissimilatory membranebound respiratory (Nar) nitrate reductases, which generate a transmembrane proton motive force allowing ATP synthesis.…”
Section: Prediction Of the Metabolic Profilesmentioning
confidence: 99%
“…Recent studies have shown that nitrogen fixation by rhizobia is not limited to legumes ( Pold et al, 2018 ; Noh et al, 2019 ), but is found in other non-leguminous higher plants, including sugarcane ( Zhao et al, 2020 ). In addition, the relative abundance of Burkholderiales was high ( Figure 4B ), and Burkholderiales have been shown to play an important role in nitrogen input to newly colonized soils ( Ortiz et al, 2020 ). In the cluster modules of the co-occurrence network of the two intercropping patterns, the number of ASVs was greater and Alphaproteobacteria, Betaproteobacteria, and Verrucomicrobia were more abundant in the ZZ9 than in the ZZ1 intercropping system ( Figure 5B ).…”
Section: Discussionmentioning
confidence: 99%